2016
DOI: 10.1007/s00330-016-4411-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of pulmonary vein and left atrial anatomical variants in atrial fibrillation patients for catheter ablation with cardiac CT

Abstract: • PVs variants are helpful for providing anatomical road map to ablation. • PV variants are common. • DSCT could recognize these anatomic features before ablation as a non-invasive imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 36 publications
5
35
1
2
Order By: Relevance
“…Second, our study measured AP, SI diameter, area, and ostial index of PVs, leading to the following five points: ostial sizes of superior PVs are larger than those of inferior PVs; ostial sizes of right PVs are larger than those of left PVs; the ostial size of CLT is the largest; the ostial size of RMPV is the smallest; and superior PV, inferior PV, and RMPV ostia on the right tend to be more circular, whereas left common ostia tend to have a more oval shape. These five points are consistent with previous studies (8,11,16,20), but afford more information. PV ostial size facilitated the selection of the size of catheters and selection of appropriate energy to avoid stenosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Second, our study measured AP, SI diameter, area, and ostial index of PVs, leading to the following five points: ostial sizes of superior PVs are larger than those of inferior PVs; ostial sizes of right PVs are larger than those of left PVs; the ostial size of CLT is the largest; the ostial size of RMPV is the smallest; and superior PV, inferior PV, and RMPV ostia on the right tend to be more circular, whereas left common ostia tend to have a more oval shape. These five points are consistent with previous studies (8,11,16,20), but afford more information. PV ostial size facilitated the selection of the size of catheters and selection of appropriate energy to avoid stenosis.…”
Section: Discussionsupporting
confidence: 92%
“…Contradictory suggestions have been made about whether the prevalence of accessory PV is significantly different from common PV or not. Chen et al suggested that RMPV was the most common variant (20), and Kanaji et al found that the most common variant was a common PV (21). However, our study found that the prevalence of accessory PV is equal to common PV.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Prior studies have investigated PV anatomy with focus on branching pattern, composition, size and ridges [15,16,27]. For comparison, McLellan, et al [16] describe in their study the dimensions of the PV ostia in a group of patients with AF with similar size distribution as in our study.…”
Section: Pulmonary Vein Cross-sectional Areamentioning
confidence: 60%
“…Actually, PV variants are not rare mainly including common ostia and additional PVs. According to the available data, the left common pulmonary vein (LCPV) was found to be one of the most common variants with prevalence ranging from 7.5% to 43% among different studies . It has been reported that an LCPV was a consistent source of arrhythmogenic atrial ectopy which might predispose to AF .…”
Section: Introductionmentioning
confidence: 99%